DUALISME KEBIJAKAN PENCEGAHAN COVID-19 DI PERBATASAN ENTIKONG KABUPATEN SANGGAU PROVINSI KALIMANTAN BARAT 2021 - Wuysang, Julia Magdalena; Iriansyah, Adibrata (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2023)
Entikong District, Sanggau Regency, West Kalimantan Province is one of the border areas of Indonesia and Malaysia. There is an Entikong Cross-Border Post (PLBN) in Entikong District. The Entikong area has also felt the impact of the Covid-19 pandemic. To prevent the spread of the Covid-19 virus in Entikong, the government issued two policies. The first policy is to close the border. Although closed, the border is still open for Indonesian citizens who want to return to Indonesia and foreign nationals who have visas and certain conditions. The second policy is the implementation of micro-based Community Activity Restrictions (PPKM). There are two conflicting policies where the border is closed but open to Indonesian citizens such as returning Indonesian migrant workers and foreigners with certain visas, on the other hand the Entikong community is restricted in their movement due to PPKM. Of course, these two policies will greatly impact the people in the Entikong border area.